The Transpolar Drift Influence on the Arctic Ocean Silicon Cycle - Liguori, Bianca T. P.; Ehlert, Claudia; Nöthig, Eva‐Maria; van Ooijen, Jan C.; Pahnke, Katharina; Ehlert, Claudia; 1 Marine Isotope Geochemistry Institute for Chemistry and Biology of the Marine Environment (ICBM) University of Oldenburg Oldenburg Germany; Nöthig, Eva‐Maria; 2 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; van Ooijen, Jan C.; 3 NIOZ Royal Netherlands Institute for Sea Research Department of Ocean Science (OCS) University of Utrecht Utrecht The Netherlands; Pahnke, Katharina; 1 Marine Isotope Geochemistry Institute for Chemistry and Biology of the Marine Environment (ICBM) University of Oldenburg Oldenburg Germany (Journal of Geophysical Research: Oceans, 2021)
During most of the year, diatom production in the ice‐covered Central Arctic Ocean (CAO) is limited by light availability and nutrient supply. Therefore, biological production is thought to be generally low, with higher biological production at the sea ice edge and over partially ice‐free shelf areas. The major surface ocean current in the CAO is the Transpolar Drift (TPD), which transports sea ice and water from the rivers and shelves of the Laptev and the East Siberian Seas across the CAO toward the Fram Strait, carrying high amounts of terrestrial‐derived material over long distances. We used Si isotopes (δ30Si) to better understand the difference between lower and higher biological production areas and how the TPD potentially affects the Si cycle in the CAO. Our data show low dissolved Si concentrations ([DSi]) paired with high values of δ30Si‐DSi in all surface samples indicating fractionation by diatoms. Specifically, outside the TPD influence, all nutrients were depleted and supply was limited due to stratified conditions, thus preventing further phytoplankton growth in the area during the sampling time in late summer‐early fall. In contrast, under the TPD influence, diatom primary production was limited by low nitrate and strongly limited by light due to the presence of sea ice, even though [DSi] values were much higher than outside the TPD. Based on δ30Si, we could identify low but measurable DSi utilization in the TPD, potentially highlighting the importance of sea ice‐attached diatoms transported to the CAO via the TPD for the Si cycle in this region. Plain Language Summary: The growth of siliceous microalgae (diatoms) in the ice‐covered Central Arctic Ocean (CAO) can be limited by light and nutrient availability. Due to the limiting conditions, diatom growth is considered to be generally low, with highest growth rates at the sea ice edge and over partially ice‐free coastal areas. The major surface water current in the CAO is the Transpolar Drift (TPD), carrying ice and water from rivers and coastal ...